Eksplorasi Pendekatan Statistik dalam Pendidikan Bahasa Arab: Tinjauan Komprehensif terhadap Kontribusi dalam Penelitian Akademis - Abdurrahman Rifki; M. Mansyur (Universitas Al-Amien Prenduan, 2022)
This research aims to explore the statistical approach in Arabic language education. The study utilizes a qualitative approach with a literature review methodology focusing on scholarly works discussing the topic. Data sources include academic literature such as reference books and published journal articles. The data analysis method employed is content analysis. The results of this research indicate that the exploration of statistical approaches in Arabic language education can measure student achievement, teaching method effectiveness, and curriculum evaluation. The primary contribution of the statistical approach lies in its ability to personalize learning. Through the analysis of individual student data, instructors can identify learning styles, strengths, and weaknesses of each student, providing opportunities to develop more tailored teaching strategies.